2017
DOI: 10.3389/fphar.2017.00132
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Ameliorates Cisplatin-Induced Nephrotoxicity and Potentiates Its Anticancer Activity in SD Rats: Potential Role of Curcumin in Breast Cancer Chemotherapy

Abstract: Breast malignant neoplastic disease is one of the most complex diseases, as it is a multifactorial disease in which virtually all the targets are instantly or indirectly inter-reliant on each other. Cisplatin (CIS), an inorganic antineoplastic agent is widely utilized in the treatment of various solid tumors including breast cancer. Despite everything, its clinical use is limited, due to ototoxicity, peripheral neuropathy, and nephrotoxicity. The present work was directed to assess the combined result of curcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 36 publications
1
52
0
1
Order By: Relevance
“…Histopathological evaluation of breast tissue showed that cellular degeneration, necrosis, and hemorrhage were severe-very severe in the cisplatin administered group. However, none of these pathological findings occurred in the CRC+ cisplatin group 19 . Our study also showed that oxidant activity (MDA) was high and antioxidant activity (GSH, SOD, GPx, and CAT) was low in the uterus of rats treated with CYC; however in the uterus of the rats in the CRC+CYP group oxidant activity was low and antioxidant activity was high.…”
Section: ■ Discussionmentioning
confidence: 87%
“…Histopathological evaluation of breast tissue showed that cellular degeneration, necrosis, and hemorrhage were severe-very severe in the cisplatin administered group. However, none of these pathological findings occurred in the CRC+ cisplatin group 19 . Our study also showed that oxidant activity (MDA) was high and antioxidant activity (GSH, SOD, GPx, and CAT) was low in the uterus of rats treated with CYC; however in the uterus of the rats in the CRC+CYP group oxidant activity was low and antioxidant activity was high.…”
Section: ■ Discussionmentioning
confidence: 87%
“…Therefore, identifying substances that reverse the pathological changes and recover function is critical. Based on biochemical markers, curcumin is one such substance with the capacity to reverse kidney dysfunction and control nephrotoxicity …”
Section: Resultsmentioning
confidence: 99%
“…Based on biochemical markers, curcumin is one such substance with the capacity to reverse kidney dysfunction and control nephrotoxicity. 48,51,79…”
Section: Histopathological Changesmentioning
confidence: 99%
“…PPARγ pathway activation was found to have a synergistic effect with chemotherapy and radiation therapy. In breast cancer cells, increasing the expression of PPARγ could enhance the cytotoxic effect of cisplatin 38. PPARγ activation could also increase the effects of radiation-induced heart injury 39.…”
Section: Discussionmentioning
confidence: 99%